REM sleep behavior disorder (RBD) - Hu, Michele T. (Neurobiology of disease, 2020)
Since its first description in 1986 by Dr. Carlos Schenck, and his group's subsequent report of the delayed emergence of a Parkinsonian disorder in idiopathic RBD patients one decade later, RBD has emerged in recent years as one of the most promising markers of prodromal Parkinson's (References 2, 3). RBD is present in 25–58% of patients with Parkinson's disease and up to 90% of those with Dementia with Lewy Bodies (DLB) or Multiple System Atrophy (MSA). In a substantial proportion of these patients RBD onset occurs before motor symptoms. Critically, when seen in isolation, RBD is a highly specific marker of future synucleinopathy: long-term cohort studies indicate that more than 80% of people who develop isolated RBD will go on to develop an alpha-synuclein related neurodegenerative disorder. Recently, the largest ever study of 1280 polysomnographically-diagnosed RBD subjects from 24 International RBD Study Group sleep centres by a single author group, found an overall conversion rate from iRBD to an overt neurodegenerative syndrome of 6.3% per year. RBD is therefore common, representative of a large proportion of sporadic disease, and provides a unique window for the study of prodromal neurodegeneration, whether it be Parkinson's or Dementia.